Association between electronic equipment in the bedroom and sedentary lifestyle, physical activity, and body mass index of children - Gerson Luis de Moraes Ferrari; Timóteo Leandro Araújo; Luis Carlos Oliveira; Victor Matsudo; Mauro Fisberg (Brazilian Society of Pediatrics, 2015)
Objective: To describe the association between electronic devices in the bedroom with sedentary time and physical activity, both assessed by accelerometry, in addition to body mass index in children from São Caetano do Sul. Methods: The sample consisted of 441 children. The presence of electronic equipment (television, personal computer, and videogames) in the bedroom was assessed by a questionnaire. For seven consecutive days, children used an accelerometer to objectively monitor the sedentary time and moderate‐to‐vigorous physical activity. Body mass index was categorized as suggested by the World Health Organization. Results: Overall, 73.9%, 54.2% and 42.8% of children had TV, computer, and videogames in the bedroom, respectively, and spent an average of 500.7 and 59.1 min/day of sedentary time and moderate‐to‐vigorous physical activity. Of the children, 45.3% were overweight/obese. Girls with a computer in the bedroom (45 min/day) performed less moderate‐to‐vigorous physical activity than those without it (51.4 min/day). Similar results were observed for body mass index in boys. Moderate‐to‐vigorous physical activity was higher and body mass index was lower in children that had no electronic equipment in the bedroom. Presence of a computer (β = −4.798) and the combination TV + computer (β = −3.233) were negatively associated with moderate‐to‐vigorous physical activity. Videogames and the combinations with two or three electronic devices were positively associated with body mass index. Sedentary time was not associated with electronic equipment. Conclusion: Electronic equipment in the children's bedroom can negatively affect moderate‐to‐vigorous physical activity and body mass index regardless of gender, school, and annual family income, which can contribute to physical inactivity and childhood obesity.